Corticomuscular coherence in asymptomatic first‐degree relatives of patients with essential tremor. Issue 5 (13th March 2013) - Raethjen, Jan; Muthuraman, Muthuraman; Kostka, Achim; Nahrwold, Martin; Hellriegel, Helge; Lorenz, Delia; Deuschl, Günther
<x xml:space="preserve">Abstract</x> Background Essential tremor (ET) follows an autosomal dominant type of inheritance in the majority of patients, yet its genetic basis has not been identified. Its exact origin is still elusive, but coherence measurements between electromyography tremor bursts and electroencephalography unequivocally demonstrate a correlation. Methods We tested these measurements in 37 healthy first‐degree relatives (children) of patients with essential tremor (ET) and a group of 37 age‐matched and sex‐matched controls. Pooled coherence spectra of the maximally coherent electroencephalogram electrodes were computed for ET relatives and controls. Results The maximal coherence and its frequency were significantly higher in ET relatives than in controls during the pinch grip task and during slow hand movements. Electromyography amplitude (root‐mean‐square) was slightly but significantly greater in ET relatives, whereas 2‐Hz to 40‐Hz power and spectral peak frequency were not different. Conclusions The presymptomatic alteration in corticomuscular interaction may reflect a role of genetic factors. © 2013 Movement Disorder Society